Telehealth-Based Self-Management in Stroke Patients: A Systematic Review - Sespa, Elya; Kariasa, I Made (Indonesian Journal of Global Health Research, 2024)
Stroke is a clinical condition in the form of focal and global neurological deficits that develop rapidly and cause death, characterized by blockage and rupture of blood vessels. The 2022 World Stroke Organization annual report states that 12.2 million people worldwide experienced a stroke and 6.6 million of them died, the prevalence of stroke increased by 85%, deaths due to stroke increased by 43% and people with disabilities (DALYs) due to stroke increased by 32%. The problems faced by stroke sufferers are likely to continue to increase and post-stroke complications need to be treated in order to extend life expectancy better. In stroke care, emphasis is placed on intensive medical care and rehabilitation benefits in the acute phase, but care and support in the later stages is just as important as treatment acute phase. People who have long-term health conditions, such as stroke patients, should learning new behaviors or adapting lifestyle to suit their needs. Improving self-management is an important challenge for service systems health worldwide for survival in long-term conditions. Telehealth provides a viable alternative in healthcare, helping clients manage their conditions through improved self-care and access to education and support systems. Additionally, clients and healthcare professionals can exchange important clinical information remotely for the management and support of patients with chronic diseases. This research aims to (1) identify the intervention components of self-management programs for stroke sufferers, (2) identify types of telehealth based self-management programs, and (3) identify the impact of providing telehealth-based self management programs for stroke sufferers. This research uses a systematic review design with the PRISMA flow diagram. Researchers used PICO, articles published from 2014 to May 2024 in English. Searches came from 5 online databases, namely "PubMed", "ProQuest", "Science Direct", "Scopus", and "Embase". Research used the Research used the physiotherapy evidence database Research used the physiotherapy evidence database skala tool to assess the quality of research article. The initial search yielded 422 articles that were further screened. There are 21 articles for eligibility assessment. After full text review, 8 articles remained that met the inclusion and exclusion criteria and were used for this systematic review. Eight high-quality articles support telehealth-based self-management as an effective method for caring for patients with stroke. Telehealth-based self-management intervention as an alternative method for stroke sufferers.